Adenosine A1 Receptors Participate in Excitability Changes after Cortical Epileptic Afterdischarges in Immature Rats - Pavel Mareš; Libor Uttl; Martina Laczó; Zina BenSalem; Kateřina Vondráková; Petr Fábera; Grygoriy Tsenov; Hana Kubová (MDPI AG, 2023)
Background: Postictal refractoriness, i.e., the inability to elicit a new epileptic seizure immediately after the first one, is present in mature animals. Immature rats did not exhibit this refractoriness, and it is replaced by postictal potentiation. In addition to the immediate postictal potentiation, there is a delayed potentiation present at both ages. These phenomena were studied using cortical epileptic afterdischarges as a model. Objective: We aimed to analyze participation of adenosine A1 receptors in postictal potentiation and depression. Methods: Adenosine A1 receptors were studied by means of Western blotting in the cerebral cortex with a focus on the age groups studied electrophysiologically. Stimulation and recording electrodes were implanted epidurally in 12- and 25-day-old rats. The first stimulation always induced conditioning epileptic afterdischarge (AD), and 1 min after its end, the stimulation was repeated to elicit the second, testing AD. Then, the drugs were administered and paired stimulations were repeated 10 min later. A selective agonist CCPA (0.5 and 1 mg/kg i.p.) and a selective antagonist DPCPX (0.1, 0.5 and 1 mg/kg i.p.) were used to examine the possible participation of adenosine A1 receptors. Results: Control younger animals exhibited potentiation of the testing AD and a moderate increase in both conditioning and testing ADs after an injection of saline. The A1 receptor agonist CCPA shortened both post-drug ADs, and neither potentiation was present. The administration of an antagonist DPCPX resulted in marked prolongation of the conditioning AD (delayed potentiation), and the second testing AD was shorter than the post-drug conditioning AD, i.e., there was no longer immediate potentiation of ADs. To eliminate effects of the solvent dimethylsulfoxide, we added experiments with DPCPX suspended with the help of Tween 80. The results were similar, only the prolongation of ADs was not as large, and the testing ADs were significantly depressed. The older control group exhibited a nearly complete suppression of the first testing AD. There was no significant change in the conditioning and testing ADs after CCPA (delayed potentiation was blocked). Both groups of DPCPX-treated rats (with DMSO or Tween) exhibited significant augmentation of delayed potentiation but no significant difference in the immediate depression. Adenosine A1 receptors were present in the cerebral cortex of both age groups, and their quantity was higher in 12- than in 25-day-old animals. Conclusions: An agonist of the A1 receptor CCPA suppressed both types of postictal potentiation in 12-day-old rats, whereas the A1 antagonist DPCPX suppressed immediate potentiation but markedly augmented the delayed one. Immediate postictal refractoriness in 25-day-old rats was only moderately (non-significantly) affected; meanwhile, the delayed potentiation was strongly augmented.